Adiponectin DNA methylation in South African women with gestational diabetes mellitus: Effects of HIV infection. - Stephanie Dias; Sumaiya Adam; Yoonus Abrahams; Paul Rheeder; Carmen Pheiffer (PLoS ONE, 2021)
DNA methylation is increasingly recognized as a potential biomarker of metabolic disease. However, there is limited information on the impact of human immunodeficiency virus (HIV) infection on the candidacy of DNA methylation to serve as molecular biomarkers. This study investigated the effect of HIV infection on DNA methylation patterns in the peripheral blood of South African women with (n = 95) or without (n = 191) gestational diabetes mellitus (GDM). DNA methylation levels at eight CpG sites in the adiponectin gene (ADIPOQ) promoter were measured using bisulfite conversion and pyrosequencing. Differences between HIV negative (-) and positive (+) women were observed. In HIV- women, methylation at CpG -3400 was lower in GDM+ women compared to those with normoglycemia (8.5-fold; p = 0.004), and was associated with higher fasting glucose (β-co-efficient = 0.973; p = 0.006) and lower adiponectin (β-co-efficient = -0.057; p = 0.014) concentrations. These associations were not observed in HIV+ women. In silico analysis showed that Transcription Factor AP2-alpha is able to bind to the altered CpG site, suggesting that CpG -3400 may play a functional role in the regulation of ADIPOQ expression. Our findings show that DNA methylation differs by HIV status, suggesting that HIV infection needs to be taken into consideration in studies exploring DNA methylation as a biomarker of GDM in high HIV prevalence settings.